Women scientists in China: current status and aspirations. Issue 10 (9th June 2021) - Gu, Chao
Abstract: Throughout history, gender inequality has persisted in most parts of the world. Since the founding of the People's Republic of China (PRC) in 1949, substantial progress has been made towards gender equality in China. Today, a large number of Chinese women scientists are making significant contributions to advance science. However, are they facing gender discrimination in hiring and promotion? Do they have access to the same opportunities as their male colleagues? What are the potential approaches to further promote gender equality in China's scientific community given myriad unfavorable social factors? Recently, NSR invited five Chinese female scientists and two gender experts to discuss these issues. Here are their observations and suggestions. Bing Liu Professor at the Department of the History of Science, Tsinghua University Jun Lu Senior Engineer at Beijing Institute of Tracking and Telecommunications Technology, and Deputy Chief Designer of BeiDou Grounded Test and Validation System Chih-chen Wang Professor at the Institute of Biophysics, Chinese Academy of Sciences Hongyang Wang President of the China Women's Association for Science and Technology (CWAST), Director of the National Center for Science in Liver Cancer Xiaoyun Wang C. N. Yang Professor at the Institute for Advanced Study, Tsinghua University Yan Zheng Chair Professor at the School of Environmental Science and Engineering, Southern University of Science and Technology Wenpei Tang (Chair) Professor at the School of Health Humanities, Peking University